Social political narratives during the first decade of transition to democracy in Chile: Intellectual political field and performativity, 1990-1998 - Moyano, Cristina (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
This article makes a historical overview of the main transformations of the political-intellectual field during the transition years, taking as its axis the one that was configured in the eighties during the military dictatorship, to analyze how the political-social narratives were transformed, understood as interpretive frames of "reality", which is in permanent dispute and construction. Thus, through a methodology that recovers the historicity of the texts, the structural changes and the contents of these narratives will be analyzed, particularly those that gave meaning to the experience of the transition from the concertationist intelligentsia and those that acted as referents against the hegemonic, shaping the so-called narratives of discomfort.